Digital transformation in human resource management practices: a systematic meta-analysis of the industrial era 4.0 - Ageng Nugroho; Otti Wulandhari (Enrichment : Journal of Management, 2025)
Digital transformation has brought a paradigmatic shift in human resource management practices in the Industry 4.0 era, shifting HR functions from conventional administrative orientation to the role of technology-based strategic partners. This study adopts a systematic meta-analysis approach with a qualitative meta-synthesis methodology to analyze the characteristics, determinant factors, and implications of human resource digital transformation based on ten studies for the 2022-2025 period. The results of the analysis identified that the application of artificial intelligence technology, big data analytics, and digital learning platforms improved operational efficiency, accelerated decision-making, and substantially accelerated employee competency development. Crucial success factors include executive leadership support, technology infrastructure readiness, workforce digital competencies, and adaptive organizational culture. Key challenges include data security, employee privacy, resistance to change, and the risk of depersonalizing work interactions. This study recommends a holistic implementation strategy that integrates organizational readiness assessments, sustainable digital literacy programs, and structured change management to achieve a sustainable and human-oriented digital transformation of human resources in the face of the complexities of the contemporary digital age